2021
DOI: 10.1590/1806-9282.67.2.20200716
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome associated with SARS-CoV-2 infection: a scoping review

Abstract: BACKGROUND: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections can affect the nervous system, triggering problems such as the Guillain-Barre Syndrome (GBS), an association that can bring complications to the patient. OBJECTIVE: This scoping review aimed to clarify the clinical features and analyze patients with GBS associated with SARS-CoV-2 infection, looking at morbidity, mortality, and neurological outcomes. SEARCH STRATEGY: The search was conducted through Medline, Web of Science, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
(179 reference statements)
0
2
0
5
Order By: Relevance
“…Alterações de curto prazo (agudas, no durante e pós-COVID-19) incluem alterações do olfato (anosmia, hiposmia e parosmia), paladar (ageusia, hipogeusia e disgeusia) e visão, delirium e alterações cerebrovasculares e obstrutivas agudas (8,(51)(52)(53). São diversas as alterações de curto prazo que podem se estender para um mais longo prazo, incluindo AVC, polineurite, alterações de movimento e comportamento, transtornos de humor e ansiedade, psicose, catatonia, déficit cognitivo, alterações neurológicas com impactos em comportamentos sociais, estresse e síndrome pós-traumática e a SGB e outras síndromes neurológicas (29,31,35,38,39).…”
Section: Sars-cov-2 E As Definições De Complicações E Sequelas Neurol...unclassified
See 2 more Smart Citations
“…Alterações de curto prazo (agudas, no durante e pós-COVID-19) incluem alterações do olfato (anosmia, hiposmia e parosmia), paladar (ageusia, hipogeusia e disgeusia) e visão, delirium e alterações cerebrovasculares e obstrutivas agudas (8,(51)(52)(53). São diversas as alterações de curto prazo que podem se estender para um mais longo prazo, incluindo AVC, polineurite, alterações de movimento e comportamento, transtornos de humor e ansiedade, psicose, catatonia, déficit cognitivo, alterações neurológicas com impactos em comportamentos sociais, estresse e síndrome pós-traumática e a SGB e outras síndromes neurológicas (29,31,35,38,39).…”
Section: Sars-cov-2 E As Definições De Complicações E Sequelas Neurol...unclassified
“…De fato, tem sido mostrado que a autoimunidade pode envolver o mimetismo molecular, em que as reações cruzadas de anticorpos com estruturas do próprio hospedeiro, como mielina, glia e β-2glicoproteínas, semelhantes aos epítopos do SARS-Cov-2, podem levar ao ataque destes componentes do SNC (1). Isto pode causar desmielinização e danos associados, como visto em certas síndromes pós-COVID-19 (1,39).…”
Section: Aspectos Patogênicos E Imunológicos Das Complicações E Seque...unclassified
See 1 more Smart Citation
“…There is a discrepancy between the search dates given under "Information sources" (until April 2020) and the search date given under "Search" (until June 26) without mentioning the year 1 . This ambiguity should be removed.…”
mentioning
confidence: 98%
“…
Dear Editor, We read with interest the review article by Medeiros et al 1 about patients with SARS-CoV-2-associated Guillain-Barre syndrome (SAG) collected via a search of various databases. It was found that the main manifestations of SAG were fever, coughing, dyspnea, sore throat, ageusia, anosmia, and respiratory failure, in addition to paresthesias of the upper and lower limbs, quadruparesis, facial diplegia, areflexia, asthenia, mastoid pain, acute ataxia, fatigue, numbness, dysphagia, and moderate low back pain 1 .
…”
mentioning
confidence: 99%